2011
DOI: 10.4028/www.scientific.net/kem.488-489.65
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lamb Wave Interaction with Fatigue Crack in Thin Al Sheet

Abstract: The phenomenon of the Lamb wave interaction with fatigue crack in Al2024-T3 sheet was investigated at cyclic loading. Mentioned effect is associated with the crack open/close that change acoustic impedance of a crack. Analytical simulation of fatigue crack opening using the generalized Dugdale’s model of a crack in thin plate shows good accordance between the intensity of ultrasonic signal and a crack opening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Effect of crack opening/closing was reliably fixed. The same effect for a relatively long fatigue crack in a thin flat samples of aluminum alloy was investigated in the articles [9][10][11]. It is demonstrated that there is a stable correlation between the size of the crack and the amplitude of the transmitted or reflected signal.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Effect of crack opening/closing was reliably fixed. The same effect for a relatively long fatigue crack in a thin flat samples of aluminum alloy was investigated in the articles [9][10][11]. It is demonstrated that there is a stable correlation between the size of the crack and the amplitude of the transmitted or reflected signal.…”
Section: Introductionmentioning
confidence: 86%
“…Here the essential results of FCOC effect are reproduced from [9][10][11]. The Al2024-T3 1 mm thickness sample equipped by two PZT was used.…”
Section: Some Main Regularities Of the Crack Opening / Closing To The...mentioning
confidence: 99%
See 1 more Smart Citation
“…6 The interaction of Lamb waves with fatigue crack opening and closing effect due to the differential loading was investigated by Pavelko et al in an aluminium panel, where they found a significant decrease in Lamb wave amplitude (peak to peak voltage) in the loaded versus the unloaded state. 7 Pavelko also used experimental and numerical techniques to study the interaction of Lamb waves excited at 250 kHz with the opening/closing effect of the fatigue crack due to differential loading on an aluminium panel. He found the presence of a threshold load above which the intensity of the transmitted signal did not change with increased loading.…”
Section: Concepts Of Damage Index and Damage Matrix Are Not New Ihnmentioning
confidence: 99%